Complications of patients with hematologic malignancies in a selected Iranian population - Shadbahr Shayeghi; mahtab Hamzeh; Ahmad Tamaddoni; sorayya Khafri; farida abesi (Babol University of Medical Sciences, 2023)
Background: Hematologic malignancies in childhood and their treatments can cause dental anomalies and jaw bone abnormalities; therefore, the aim of this study was to assess the prevalence of these disorders in children. Methods: This cross-sectional study was conducted on all children diagnosed with hematologic malignancies that referred to in Amirkola Children's Hospital from 2011 to 2018. All of children underwent clinical evaluation in a Dental Radiology Clinic and panoramic imaging was performed. The radiographs were examined for dental anomalies and jaw bone abnormalities. The data were analyzed by descriptive analysis using chi-square, Mann-Whitney and Kruskal-Wallis with a 95% confidence interval. Results: The study population consisted of 32 children and 9.46% of these patients showed intraoral signs in clinical evaluations. Panoramic radiographs indicated dental anomalies in 12 (63.9%) and jaw bone abnormalities in 17 (89.4%) patients. The most common dental anomaly and bone abnormality were taurodontism and changes in lamina dura, respectively. By measuring the mandibular cortical index (MCI), it was revealed that 13 had osteopenia, in which 4 of them had severe osteopenia (osteoporosis). The statistical analysis demonstrated that there was a significant difference between the incidence of osteoporosis and changes in lamina dura with the gender (p<0.05). Conclusion: Due to early onset of osteopenia and osteoporosis and the presence of dental and bone abnormalities in half of study population, early assessment of their clinical and radiographic condition can be helpful in the prevention and the early treatment of their oral complications.